2014
DOI: 10.1016/j.cortex.2012.09.005
|View full text |Cite
|
Sign up to set email alerts
|

The anatomy of fronto-occipital connections from early blunt dissections to contemporary tractography

Abstract: The occipital and frontal lobes are anatomically distant yet functionally highly integrated to generate some of the most complex behaviour. A series of long associative fibres, such as the fronto-occipital networks, mediate this integration via rapid feed-forward propagation of visual input to anterior frontal regions and direct top-down modulation of early visual processing. Despite the vast number of anatomical investigations a general consensus on the anatomy of fronto-occipital connections is not forthcomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
191
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 219 publications
(198 citation statements)
references
References 52 publications
6
191
0
1
Order By: Relevance
“…However, prior diffusion tensor imaging studies with blind individuals argue against this possibility. The frontal and occipital lobes are connected by the inferior fronto-occipital fasciculus and by a portion of the superior longitudinal fasciculus extending into the occipital lobe (Forkel et al, 2014). Contrary to the hypothesis of increased anatomical connectivity, inferior fronto-occipital fasciculus shows reduced white matter integrity in blindness (Shu, Liu, et al, 2009).…”
Section: Implications Of Resting State Group Differences For Anatomy mentioning
confidence: 85%
“…However, prior diffusion tensor imaging studies with blind individuals argue against this possibility. The frontal and occipital lobes are connected by the inferior fronto-occipital fasciculus and by a portion of the superior longitudinal fasciculus extending into the occipital lobe (Forkel et al, 2014). Contrary to the hypothesis of increased anatomical connectivity, inferior fronto-occipital fasciculus shows reduced white matter integrity in blindness (Shu, Liu, et al, 2009).…”
Section: Implications Of Resting State Group Differences For Anatomy mentioning
confidence: 85%
“…While both the UF and ILF have relatively long histories, the MdLF has been scarcely considered until very recently and its potential function remains poorly understood. Additionally, the IFOF has become increasingly popular in the current literature but it is riddled with a debate over its very existence, as is ILF (Forkel et al, 2014;Schmahmann & Pandya, 2007;Tusa & Ungerleider, 1985). There is also considerable controversy over tract origins, terminations and routes.…”
Section: The White Matter Tracts Of the Ventral Semantic Language Netmentioning
confidence: 95%
“…Although many studies have documented the presence of this pathway using both gross dissection and tractography methods (Axer et al, 2012;Catani et al, 2002;Forkel et al, 2014;Martino, Brogna, et al, 2010;Sarubbo et al, 2013), based on its absence in primate tracer studies, some researchers have argued that the IFOF is not a true tract but a misidentification of other ventral pathways Saur et al, 2008;Schmahmann & Pandya, 2007). However, while there has been no evidence for the existence of the IFOF in primates (Schmahmann & Pandya, 2007), studies have described a primate EmC which tracks from the frontal lobe to posterior regions in the superior temporal sulcus, following a course similar to the IFOF (Schmahmann & Pandya, 2009).…”
Section: Inferior Fronto-occipital Fasciculusmentioning
confidence: 99%
“…Bauer's patient suffered a bilateral occipitotemporal traumatic hemorrhage, while Habib's patient suffered a right occipitotemporal infarction. The authors concluded that the visual hypoemotionality resulted from the interruption of the fiber systems that connect the visual association cortices with the anterior temporal lobes 1 (Forkel et al, 2014;Tusa & Ungerleider, 1985).…”
Section: Discussionmentioning
confidence: 98%
“…The other system is direct and composed of fast conducting long association fibers that connect the ventromedial extrastriate occipital cortex with (a) the anterior lateral and medial temporal cortices, and (b) the orbitofrontal and frontopolar cortices. This system has long been known as the inferior fronto-occipital fascicle (Forkel et al, 2014). The projections of both fiber systems are reciprocal.…”
Section: Discussionmentioning
confidence: 99%